INDONESIAN EGGS ARE PRICIER THAN THOSE IN AUSTRALIA - Eka Krisna Santoso; Muhammad Ikhsan Alif (TECHNOBIZ : International Journal of Business, 2023)
In measuring a nation’s wealth, we can observe from how much purchasing power its citizens have.  The more things they can buy with the same value of money, the wealthier the nation is. This paper will examine the purchasing power of Indonesian citizens in buying one of their essential staples; egg. We will take a look at those having minimum wage, whether they need a higher value of money in order to purchase one kilograms of egg. To understand how powerful the purchasing power is, we will compare with Australian citizens having the minimum wage, as well. The distinction part of this paper, is that we take into account OECD’s Purchasing Power conversion rate, instead of using currency rate. After examining both samples, we obtain that people in Indonesia have lower purchasing power than those in Australia.